Survey of the Culicide community (Diptera: Culicidae) in the Caatinga Biome, Bom Jesus City, Piauí, Brazil (Research, Society and Development, 2021)
Mosquitoes are insects of great medical importance, acting as vectors of arboviruses and other pathogens that could be transmitted to humans. With the climate change many species of mosquitoes have adapted to survive in these altered conditions. The goal of this study was to describe the community of Culicidae in three gradients of environment within the Caatinga biome in the Bom Jesus municipality, Brazil. The environmental gradients included ​​native forest, rural and urban areas. Mosquitoes were collected and the following variables were analyzed: total and relative species abundance, total and relative species frequency, diversity, domain, the correlation among meteorological data, genus and the similarity between areas. The captures were made monthly for three consecutive days for a one-year period. Passive capture was performed using CDC traps placed a minimum distance of 50 meters apart in each sampling site. The mosquitoes collected were identified as: Aedeomyia spp., Aedes spp., Anopheles spp., Culex spp., Coquillettidia spp., Psorophora spp. and Uranotaenia spp. The genres Aedes, Anopheles, Culex, Coquillettidia and Psorophora were present year-round in at least one of the areas. The most abundant genres were the Anopheles and Culex, respectively. The native forest contained the highest diversity. However, the highest abundance of individuals was found in the rural areas, suggesting species adaptation to anthropized environments.  Overall, the high abundance of the genus Anopheles and Culex is a public health concern as these genres are known to be involved in the transmission of malaria, human filariasis, and arboviruses.